N/A Influence of capacity building practices on performance of Self-Help groups, projects in Nyeri County, Kenya: Influence of capacity building practices on performance of Self-Help groups, projects in Nyeri County, Kenya - Muriithi, Charles; Ndung’u, Anthony; Kidombo, Harriet (IJRDO - Journal of Social Science and Humanities Research, 2021)
Most development organizations are involved in capacity building for achieving development goals and contributing to sustainability, which is seen as a long-lasting result of capacity building. These organizations enhance or accelerate the internal process of capacity building especially in terms of specific skills through planned interventions, such as technical assistance, training courses and other actions. This study used a descriptive survey research design approach. There were a total of 237 self-help groups in Nyeri Central Sub County according to the county government statistics. The target population of the study was 3 members who are also leaders in the SHGs comprising of the chairperson, secretary and the treasurer. The sample size was 108 possible respondents. Quantitative data from close-ended questions and Likert Scales were coded and entered into Statistical Packages for Social Scientists (SPSS) Version 22.0 and analyzed using descriptive statistics. The study concluded that most SHGs members feel motivated about the capacity building techniques shared among members of their group for they enhance project success, they believe they have visionary leadership that understands well on capacity building as a result of good management leading to high levels of cohesion, commitment, trust, motivation towards their SHG’s projects performance, they were happy that members always acquire new capacity skills that the performance of SHGs projects needs and that; they are happy as members of their SHG that capacity building skills are easy to understand. The study recommends that the government, through the various agencies and ministries ensure that the capacity building techniques and related practices are well enhanced to improve their efficiency on the performance of SHGs in Nyeri County. In this case, there should be enhanced training and development of the leaders in the SHGs for this will act like a rapport towards making them understand the need towards knowledge sharing practices. The research recommends that the group leaders with the support of government officials and other group members who have diverse knowledge search for more understanding on capacity building or seek more of sharing practices. In this case, they will be in a position to help their counterparts be in a position to address project related activities in their SHGs which at the long end will have adequate knowledge through capacity building to help them do well on their projects.